Evaluating the Accuracy and Reliability of the Demirjian Method for Dental Age Assessment: A Systematic Review: Reliability of the Demirjian Method for Dental Age Assessment - Vistro, Arslan Ali; Farooqui, Saad Saud; Saeed, Muhammad Hassan; Maqbool, Ali; Ghauri, Muzaffar Qayum Khan; Dherwani, Vishal; Ahsan, Shaharyar; Khan, Muhammad Usama (Pakistan Journal of Health Sciences, 2024)
The biological age estimation performed by using dental age assessment is considered a reliable, time-saving, and time-saving technique. Dental age assessment plays an important role in various fields. Objective: To assess the accuracy and reliability of the Demirjian method in determining dental age. Methods: A systematic review with a study duration of twelve months from September 2023 to August 2024, was conducted to identify relevant literature published in fifteen years between 2010 and 2024. Comprehensive searches were performed across multiple databases, including PubMed, Google Scholar, Cochrane Library, Springer, and Science Direct. The PRISMA guidelines were strictly adhered to throughout the review process. Relevant data were extracted from these studies, and a comprehensive analysis was performed to synthesize the available evidence. Results: These results indicate Demirjian methods compared to other dental age assessment methods such as Nolla, Willem’s method showed less accuracy and reliability for dental age assessment. Conclusions: It was concluded that the Demirjian method compared to other dental age assessment methods demonstrated lesser reliability, showed less accuracy in finding the differences between dental age and chronological age, and it also overestimated dental age.